The Effect of Financial Literacy and Financial Attitude on Financial Welfare of MSME Actors in Sidoarjo City with Financial Management Behavior as an Intervening Variable: Pengaruh Literasi Keuangan dan Sikap Keuangan Terhadap Kesejahteraan Keuangan Pada Pelaku UMKM di Kota Sidoarjo Dengan Perilaku Pengelolaan Keuangan Sebagai Variabel Intervening - Miftahul Jannah; Wisnu Panggah Setiyono (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study was to determine whether the financial welfare of MSME actors in Sidoarjo can be measured through their financial behavior, where the level of financial management behavior in this study is seen based on financial literacy and one's financial attitude. This study uses primary data through a data collection process by distributing questionnaires directly (offline) or online with a non-probability sampling method with a total of 100 respondents from SMEs in Sidoarjo. The data analysis technique used is Structural Equation Modeling (SEM) with the Smart-PLS version 3.2.8 program. from this study shows that there is a positive and significant influence on financial literacy, financial attitudes, and financial management behavior on financial welfare. Financial literacy, and financial attitudes have a positive and significant influence on financial management behavior. And for the influence of the Intervening variable, it results that financial literacy and financial attitudes have an influence on financial welfare through financial management behavior.